Synergistic effect approaching record-high figure of merit in the shear exfoliated n-type Bi2O2-2xTe2xSe. (March 2020) - Pan, Lin; Liu, Wei-Di; Zhang, Jie-Yun; Shi, Xiao-Lei; Gao, Han; Liu, Qing-feng; Shen, Xiaodong; Lu, Chunhua; Wang, Yi-Feng; Chen, Zhi-Gang
Abstract: Due to the nature of high stability and eco-friendliness, layered n-type Bi2 O2 Se-based thermoelectric materials have attracted extensive research interest. In order to reduce lattice thermal conductivity and enhance thermoelectric performance of Bi2 O2 Se-based thermoelectric materials, here, we introduced Te substitution at O site into Bi2 O2-2x Te2x Se prepared by a shear exfoliation method. The induced high-density nanosized Bi2 O2 Se grains and point defects can effectively scatter both mid and short-wavelength phonons, leading to a low lattice thermal conductivity of 0.57 W m −1 K −1 at 773 K. Furthermore, Se vacancies generated by the shear exfoliation induced a high carrier concentration approaching the optimized level, and in turn lead to relatively high electrical performance. The synergistic high electrical performance and low lattice thermal conductivity secured a record-high dimensionless figure of merit, zT, of 0.69 at 773 K. This study indicates that shear exfoliation method and Te substitution are promising methods to optimize the thermoelectric properties of Bi2 O2 Se-based thermoelectric materials. Graphical abstract: With high stability, low-cost and eco-friendliness, n-type Bi2 O2 Se attracted increasing interest. Here, we discovered hierarchical structure of nano-grians, point defects, impurity interfaces in shear exfolicated Bi2 O2-2x Te2x Se can effectively scatter phonons leading to low lattice thermal conductivity of 0.57 W m −1 K −1 . With synergistically optimized electron concentration deriving from shear exfolication induced Se vacancies, the figure of merit increased to 0.69. Image 1 Highlights: Nano-grains, point defects and interfaces scatter phonons at a wide frequency range. Approaching low lattice thermal conductivity of 0.57 W m −1 K −1 . Shear exfoliation induced additional Se vacancies secured optimized carrier concentration. A record-high figure of merit, zT, of 0.69 in Bi2 O2 Se-based thermoelectric materials.